2019
DOI: 10.12775/cjfa.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intangible Factors on Profitability: Evidence From Corporations Traded at Muscat Securities Market in Oman

Abstract: The objective of this paper is to determine whether corporate financial performance may be influenced from intangible assets owned by a company and some special incurring expenditures benefiting the intangible value of the company even though such items could also be technically expensed contrary to getting capitalized. Combining the intangibles reported on the corporate balance sheets with the expenditures such as R&D, staff and advertising expenses, a variable called Calculated Value of Intangible Factors (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
1
4
0
2
Order By: Relevance
“…The results from the study have implications for the source of deposits to banks as this will significantly affect the pricing of agricultural loans. This finding is consistent with Mbao et al (2014) as well as Kaymaz and Kaymaz (2011) found that deposit rate significantly affects lending rate in their studies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results from the study have implications for the source of deposits to banks as this will significantly affect the pricing of agricultural loans. This finding is consistent with Mbao et al (2014) as well as Kaymaz and Kaymaz (2011) found that deposit rate significantly affects lending rate in their studies.…”
Section: Resultssupporting
confidence: 93%
“…This finding is consistent with Mbao et al . (2014) as well as Kaymaz and Kaymaz (2011) found that deposit rate significantly affects lending rate in their studies.…”
Section: Resultsmentioning
confidence: 86%
“…The higher the company's ROA means the higher the level of achieved profitability. Choosing ROA as a dependent variable in comparison with other indicators which characterise profitability of the enterprise is proved by its broad application by scholars Linawati and Halim (2017), Singh and Bagga (2019), Ullah (2019), Kaymaz et al (2019), Herdiyana et al (2021), Fauziyah and Djamaluddin (2021). On the other hand, ROA is used by the management of advertising agencies to adjust current managerial policies and making decisions, because ROA reflects the effectiveness of management in the context of using the company's assets at their disposal.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the gradual formation of the knowledge-based economy, in recent years, studies of the impact of intangible factors of enterprise value creation have become especially relevant. Some scholars dedicate their papers to issues of the impact of intellectual capital on the entities' profitability (Sik & Kim, 2020;Kaymaz, Yilmaz & Kaymaz, 2019;Suherman, 2017;Seo & Kim, 2020;Petković & Dordević, 2021;Lehenchuk, Tumpach, Vyhivska, Makarovych & Lehenchuk, Mateášová, Ostapchuk & Polishchuk, 2022). Other researchers analyze the effect of certain activities on the profitability of enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inovasi bagi perusahaan mampu memberikan keunggulan bersaing yang dapat berdampak positif bagi kinerja perusahaan jangka panjang. Dalam beberapa penelitian, R&D terbukti memberi dampak yang positif bagi kinerja perusahaan (Kaymaz et al, 2019;Manogna & Mishra, 2021;Shasha, 2021). Di balik manfaatnya, R&D memiliki risiko yang lebih besar dan hasil yang tidak pasti dibandingkan proyek investasi lain.…”
Section: Risetunclassified